Una evaluación a los métodos para elicitar requisitos de seguridad (2011)
Using an elicitation method can help specifying a coherent and comprehensive set of security requirements. However, usually, the common methods used to elicit functional requirements are not oriented to security requirements, therefore, the resulting set of requirements does not includes them. In this article are analyzed some methods of security requirements elicitation and is presents a proposal to select the most suitable, subsequently, some methods are selected and applied to several case studies.